Regional Convergence of Fertility in Russia - Shubat, Oksana Mikhaylovna (Economy of Regions, 2019)
The balance of the regions’ demographic dynamics in many ways determines the country’s sustainable demographic development. The high level of the regional fertility differentiation, historically manifested in Russia, requires the development of specific tools. These tools are necessary for analysing the regional imbalance as well as the trends of the regions’ convergence (divergence) in terms of fertility rate. The study analyses convergence of fertility in Russia. For this purpose, I developed a theoretical and methodological framework that assesses the concept of convergence at three levels: ideological and political, theoretical, and instrumental and applied. Methodological approaches to analysing the fertility’s convergence allow assessing the dynamics of the fertility’s interregional dispersion, the structural impact in the tendencies of regional convergence, as well as the changes of the regions’ ranked positions in terms of fertility. I demonstrated the methods of analysing ϭ-, ß-, γ-convergence. Further, I tested the developed tools using the data on the total fertility rate for the period from 1990 to 2016. A separate analysis was conducted for the period from 2007, when the measures aimed at supporting fertility significantly strengthened. The results of the study have demonstrated that in the historical perspective there was no fertility convergence. Moreover, there is no fertility convergence in the period of active implementation of the state measures to support fertility. Thus, the recent demographic policy is yet to produce a positive effect in relation to levelling the regional differences in fertility. I concluded that analysing the regional fertility’s convergence allows understanding the nature and prospects of the population’s reproduction processes in the country. This analysis expands the information base for making management decisions in the sphere of demographics and allows addressing the demographic problems in Russia as it contributes to the growth of effectiveness of the measures to support and stimulate fertility. The study of the so-called club convergence is a prospective direction for further research.